The Effectiveness of Green Grape Extract (Vitis vinifera) on Decreasing White Rat (Rattus novergicus) Triglycerides Levels - Arwati, Ketut Lilik; Dewi, Ni Nyoman Astika; Bekti, Heri Setiyo; Dewi, Ni Wayan Rika Kumara; Saransi, Andi Udin (Faculty of Medicine and Health Universitas Muhammadiyah Jakarta, 2022)
Background: Grapes (Vitis vinifera) are a source of antioxidants with high content of polyphenols and anthocyanins. Grape skin is rich in flavonoids. Anthocyanins and flavonoids have the effect of lowering blood triglyceride levels. Purposes: This study aimed to determine the effect of using green grape extract (GGE) in lowering triglyceride levels in the blood. Methods: Five groups of white male rats (Rattus novergicus) were divided into a negative control group (KN), positive control (KP), rats with a GGE dose of 100 mg/200g BW as P1, rats with a GGE dose of 250mg/200g BW as P2, and rats with GGE dose of 500 mg/200g BW as P3. Each group was given a hypercholesterolemic diet for five weeks. Groups P1, P2, and P3 were given GGE according to their respective doses for 14 days, then measured triglyceride levels in the blood. Results: The results showed that GGE 500mg/200g BW significantly reduced triglyceride levels in all treated mice. Conclusion: These results indicate that GGE has a great potential to treat dyslipidemia by lowering triglyceride levels in the blood.